Construction Grammar: Basic Principles and Concepts - Wasserscheidt, Philipp (Ukrainian linguistics, 2019)
The article provides an overview of Construction Grammar. First, a general survey of the basic principles and major strands of the grammatical theory is given. The main assumptions include the recognition that all linguistic knowledge is of the same type as knowledge in general and follows the same principles such as categorization, abstraction and generalization. In the second part, the presentation focuses on two important elements of construction grammar research: the concept of the construction as complex sign and the abandoning of the distinction between lexicon and grammar. Using examples from Ukrainian, the different relationships between constructions of different complexity and schematicity in the so-called constructicon – the common space of both lexical and grammatical knowledge – are described. It is shown, how abstract constructions offer slots for other elements and how these are constrained regarding form and meaning. In addition, the status of constructions as complex signs is assessed from the perspective of semantics and compositionality. It is highlighted that Construction Grammar rejects the assumption of compositionality and rather conceptualizes meaning as determined by the construction itself. At the same time, semantics is understood in an encyclopaedic sense, which renders the description of constructions highly detailed and language-specific. Information about the author:Philipp Wasserscheidt – PhD, Associate Prof., Humboldt-University of Berlin (Germany).E-mail: philipp.wasserscheidt@hu-berlin.de__________References• Beule J. de, Steels L. (2005) Hierarchy in Fluid Construction Grammars. Advances in artificial intelligence: KI 2005, Koblenz / U. Furbach. Berlin, New York : Springer, pp. 1–15.• Boas H. C. (2008) Determining the structure of lexical entries and grammatical constructions in Construction Grammar. Annual Review of Cognitive Linguistics, № 6, pp. 113–144.• Booij G. (2007а) Construction Morphology and the Lexicon. Selected proceedings of the 5th Décembrettes: Morphology in Toulouse / F. Montermini. Somerville, Mass : Cascadilla Proceedings Project, pp. 34–44.• Booij G. (2007b) The grammar of words: An introduction to linguistic morphology. Oxford, New York : Oxford University Press.• Broccias C. (2013) Cognitive Grammar. The Oxford handbook of construction grammar / T. Hoffmann et al. New York : Oxford University Press, pp. 191–210.• Bybee J. L. (2010) Language, usage and cognition. Cambridge [etc.] : Cambridge University Press.• Bybee J. L. (2013) Usage-Based Theory and Exemplar Representations. The Oxford handbook of construction grammar / T. Hoffmann et al. New York : Oxford University Press, pp. 49–69.• Casenhiser D., Goldberg A. E. (2005) Fast mapping of a phrasal form and meaning. Developmental Science, № 6, pp. 500–508.• Croft W. (2001) Radical construction grammar: Syntactic theory in typological perspective. Oxford : Oxford University Press.• Croft W. (2007) Construction Grammar. The Oxford handbook of cognitive linguistics / D. Geeraerts. New York : Oxford University Press, pp. 463–508.• Diewald G. (2009) Konstruktionen und Paradigmen. Zeitschrift für germanistische Linguistik, № 3, pp. 445–468.• Fillmore C. J. (1988) The Mechanisms of “Construction Grammar”. Proceedings of the Fourteenth Annual Meeting of the Berkeley Linguistics Society, pp. 35–55.• Fillmore C. J. (2013) Berkeley Construction Grammar. The Oxford handbook of construction grammar / T. Hoffmann et al. New York : Oxford University Press, pp. 111–132.• Fischer K., Stefanowitsch A. (2006) Konstruktionsgrammatik : Ein Überblick. Konstruktionsgrammatik. Von der Anwendung zur Theorie / K. Fischer et al. Tübingen : Stauffenburg, pp. 3–17.• Fried M. (2013) Principles of constructional change. The Oxford handbook of construction grammar / T. Hoffmann et al. New York : Oxford University Press, pp. 419–437.• Fried M. (2015) Construction Grammar. Syntax – Theory and Analysis. An international Handbook / A. Alexiadou et al. Berlin : De Gruyter Mouton.• Goldberg A. E. (1995) Constructions: A construction grammar approach to argument structure. Chicago : University of Chicago Press.• Goldberg A. E., Casenhiser D. (2006) English Constructions. The handbook of English linguistics / B. Aarts et al. Malden, MA, Oxford : Blackwell Publishing, pp. 343–355.• Goldberg A. E. (2006) Constructions at work: The nature of generalization in language. Oxford, New York : Oxford University Press.• Goldberg A. E. (2013) Constructionist Approaches. The Oxford handbook of construction grammar / T. Hoffmann et al. New York : Oxford University Press, pp. 15–31.• Hoffmann T., Trousdale G. (2013) Construction Grammar. Introduction. The Oxford handbook of construction grammar / T. Hoffmann et al. New York : Oxford University Press, pp. 1–12.• Kay P. (1995) Construction Grammar. Handbook of pragmatics / J. Verschueren et al. Amsterdam : Benjamins, pp. 171–177.• Lakoff G. (1987) Women, fire, and dangerous things: What categories reveal about the mind. Chicago : University of Chicago Press.• Lambrecht K. (1986) Topic, Focus, and the Grammar of Spoken French: Dissertation. Berkeley : University of California.• Langacker R. W. (1986) An introduction to Cognitive Grammar. Cognitive Science, № 10, pp. 1–40.• Langacker R. W. (1987) Foundations of cognitive grammar: Theoretical Prerequisites. Stanford, Calif : Stanford University Press.• Langacker R. W. (1991) Concept, image, and symbol: The cognitive basis of grammar. Berlin, New York : Mouton de Gruyter.• Langacker R. W. (2005) Construction Grammars: cognitive, radical, and less so. Cognitive linguistics / F. J. de Ruiz Mendoza Ibáñez. Berlin, New York : Mouton de Gruyter, pp. 101–159.• Langacker R. W. (2009) Cognitive (Construction) Grammar. Cognitive Linguistics, № 1, pp. 167–176.• Michaelis L. A. (2013) Sign-Based Construction Grammar. The Oxford handbook of construction grammar / T. Hoffmann et al. New York : Oxford University Press, pp. 133–152.• Saussure F. dе, Bally C., Sechehaye A., Mauro T. de, Calvet L.-J. (1985) Cours de linguistique générale. Paris : Payot.• Schmid H.-J. (2017) Entrenchment and the Psychology of Language Learning: How We Reorganize and Adapt Linguistic Knowledge. Boston : APA and Walter de Gruyter.• Schönefeld D. (2006) Constructions. Special volume 1, Constructions all over: case studies and theoretical implications.• Steels L., Deule J. de, Wellens P. (2012) Fluid Construction Grammar on Real Robots. Language Grounding in Robots / L. Steels et al. New York : Springer, pp. 195–213.• Stefanowitsch A., Gries S. T. (2003) Collostructions: Investigating the interaction between words and constructions. International Journal of Corpus Linguistics, № 2, pp. 209–243.• Stefanowitsch A. (2011) Konstruktionsgrammatik und Grammatiktheorie. Konstruktionsgrammatik III / A. Ziem et al. Tübingen : Stauffenburg, pp. 11–25 (in German).• Traugott E. C. (2008) The grammaticalization of NP of NP Patterns. Constructions and language change / A. Bergs et al. Berlin, New York : Mouton de Gruyter, pp. 23–45.• Trousdale G. (2010) Issues in constructional approaches to grammaticalization. Grammaticalization / K. Stathi et al. Amsterdam, the Netherlands, Philadelphia : John Benjamins, pp. 51–71.• Verhagen A. (2009) The conception of constructions as complex sings: Emergence of structure and reduction to usage. Constructions and Frames, № 1, pp. 119–152.• Wasserscheidt P. (2016) Bilinguales Sprechen: Ein konstruktions-grammatischer Ansatz. Berlin: Freie Universität Berlin.• Wulff S. (2013) Words and Idioms. The Oxford handbook of construction grammar / T. Hoffmann et al. New York: Oxford University Press, pp. 274–289.
Keywords: Construction Grammar, Ukrainian, Constructions, Sign, Grammatical Theory